INTERACTION OF FOLIAR NUTRIENTS AND HERBICIDES INTO PRODUCTION - Al-ziady, S. H. A.; Hassan, D. S.; Al-Mashhadani, A. S. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
A field trial was carried out at the fields of Baghdad University - Jadriya for the first location during the summer season of 2018, while the second location was in Mishkab Rice Research Station, Al-Najaf al-ashraf governorate during the summer season of 2019. This study was aimed investigate rice (Oryza sativa cv. Anber) response to foliar application of nutrition with the use of different herbicides. The design was RCBD wihin using split plot arrangement four replicates. The nutrition treatments; (Humic acide, Seaweed, Nano fertilizer, Normal fertilization and Without fertilizer) were in main plots. Herbicides treatments (Ronstar, Oscar, Rainbow, Super flag, weed free and weedy) occupied the sub plots.The results indicated that Ronstar herbicide was superior in giving the lowest average weeds density value 6.55 and 9.60 plant m-2 respectively, and highest average of grain yield was 2.53 and 3.42 t.h-1, respectively. The normal fertilization treatment was superior gave the highest average grain yield value 3.07 and 4.13 t h-1. As for the effects of interaction, the Ronstar combination with normal fertilization gave highest grain yield value 3.55 and 4.59 t h-1, respectively. Concluded from this trial that the Ronstar herbicide is the best among the herbicides used with different fertilization treatments by achieving the highest averages with most of the studied charactristics.